Training partner selection and quality assurance in restorative justice for the criminal justice setting - Lanterman, Jennifer L. (Contemporary justice review, 2020)
Restorative justice (RJ) conferences may be used as an alternative to or in conjunction with conventional criminal justice system responses. They may yield benefits for victims, offenders, and effected communities. RJ conferences also have the potential to be counterproductive if facilitators are not properly trained or if they fail to properly implement models of practice. This paper reports on the results of a multiple-case study of RJ practitioner trainings and advances recommendations for training partner selection and quality assurance processes in the criminal justice context. The paper concludes with suggestions for future research.